The calcified Sphenomandibular ligament: case report, surgical management and literature review - Araidy, Shareef; Batshon, George; Mirochnik, Roman; Abu El-Naaj, Imad (Frontiers in Oral Health, 2025)
Calcification of the Sphenomandibular ligament (SML) is an extremely rare condition, with only three previously documented cases worldwide. This report presents the fourth known case of SML calcification in a 32-year-old male patient with a 17-year history of progressive trismus. Following a dental procedure involving a mandibular nerve block, the patient gradually developed limited mouth opening, which was resistant to conservative treatments. Imaging revealed calcification of the SML, which was confirmed intraoperatively. Surgical excision led to a significant improvement in mandibular function. This report discusses clinical presentation, diagnostic workup, surgical management, and a comprehensive literature review, emphasizing the importance of considering rare ligamentous pathologies in cases of persistent trismus.